2016
DOI: 10.1038/srep23948
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between plasma leptin levels, leptin G2548A, leptin receptor Gln223Arg polymorphisms and gestational diabetes mellitus in Chinese population

Abstract: The purposes of this study were to examine concentrations of leptin and biochemical parameters in gestational diabetes mellitus (GDM) patients and normal glucose tolerance (NGT) individuals, and also to explore the links of leptin (LEP) G2548A and leptin receptor (LEPR) Gln223Arg polymorphisms with leptin levels and GDM risk among Chinese. Our study included 357 GDM and 355 NGT individuals who were at 24~30 gestational weeks. Plasma leptin and insulin levels were analyzed by ELISA. Gene polymorphisms were geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…We also found that RBP4 levels were positively correlated with CRP and IL-6. Recent studies have demonstrated that circulating leptin [30], adiponectin [31,32], and mild inflammation [33] could lead to exaggerated insulin resistance in GDM. Consistent with those findings, we also found that inflammation markers (CRP and IL-6) and adiponectin could predict increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that RBP4 levels were positively correlated with CRP and IL-6. Recent studies have demonstrated that circulating leptin [30], adiponectin [31,32], and mild inflammation [33] could lead to exaggerated insulin resistance in GDM. Consistent with those findings, we also found that inflammation markers (CRP and IL-6) and adiponectin could predict increased risk of GDM.…”
Section: Discussionmentioning
confidence: 99%
“…We did not measure leptin levels, so we could not determine whether the LEP and LEPR polymorphisms were associated with leptin levels or whether the LEP and LEPR polymorphisms and leptin levels interacted in their associations with the outcomes in this study. Limited evidence showed that neither LEP G2548A nor LEPR Q223R polymorphisms were significantly associated with plasma leptin levels in Chinese populations [ 51 , 52 ]. Therefore, we are considering to measure serum leptin, adipokine and soluble leptin receptor concentrations in our ongoing large scale cardiovascular cohort project.…”
Section: Discussionmentioning
confidence: 99%
“…The association of polymorphisms in the leptin gene with GDM is controversial. Vaskú et al (2006) showed an association of leptin polymorphism -2548G>A with preeclampsia in GDM, but Yang et al (2016) failed to associate this polymorphism with GDM in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%